Candidemia in neonatal intensive care unit: a cause of concern - Yadav, Sarita; Dahiya, Shalley; Budhani, Diksha (International Journal of Research in Medical Sciences, 2017)
Background: Candidemia in neonates is a serious and common cause of late onset sepsis. Candida species are the third most frequent organism isolated in late onset sepsis in very low birth weight (VLBW) infants (i.e., <1,500 g). Methods: This study was performed to evaluate epidemiology, species distribution, antifungal susceptibility and outcome of candida blood stream infections at a tertiary care centre. Results: About 1-2 ml of blood was collected aseptically in suspected cases of septicaemia and inoculated in 20 ml of Brain Heart Infusion(BHI) broth. Candida species isolates were confirmed by germ tube production, chlamydospore formation on corn meal agar(HiMedia), pigmentation on Hichrome Candida differential agar (Himedia), and carbohydrate assimilation tests. Non-albicans candida spp. are of special concern, due to their high virulence and low azole susceptibility characteristics, augmenting the high mortality rates. Conclusions: The emergence on non-albicans Candida merits attention as they display higher degree of resistance to azoles and are associated with higher mortality rates. Additional studies are required to define more accurately the prevalence and sensitivity pattern of Candida spp. which may serve as a template for development of preventive and therapeutic strategies for neonatal candidemia especially at peripheral health centres.